Octahedral Cuprous Oxide Decorated Flexible Reduced Graphene Oxide Paper for Food Sensing Application. Issue 6 (17th March 2021) - Song, Runmin; Li, Zhanhong; Mishra, Rupesh K.; Wei, Pengju; Zhao, Xueling; Zhu, Zhigang
Abstract: This work presents a simple method to fabricate an octahedral cuprous oxide (Cu2 O) decorated two‐dimensional (2D) flexible rGOP electrode with filtration and electrodeposition strategies. The characteristic of the Cu2 O/rGOP electrodes was recorded by SEM, EDX, XPS, XRD, and Raman spectroscopy. The results clearly showed that Cu2 O was successfully electrodeposited on the surface of rGOP by controlling the electrodeposition potential without the introduction of any template or surfactant. The electrochemical characterizations of the Cu2 O/rGOP exhibited high electrocatalytic activity toward the reduction of H2 O2 . The linear detection range for the Cu2 O/rGOP flexible sensor was 5.0 μM to 5.5 mM, with a limit of detection of 1.27 μΜ. Subsequently, the developed flexible rGOP sensor was extended for H2 O2 detection in milk samples for avoiding milk spoilage. Such judicial preparation of rGOP as a sensing device will certainly pave the way for various other sensing applications including environmental and biomedical applications. Abstract :